Early Clinical Experience: A Way for Preparing Students for Clinical Setting - Ebrahimi, Sedigheh; Kojuri, Javad; Ashkani-Esfahani, Soheil (Galen Medical Journal, 2013)
Background: Various methods are used to improve the quality and usefulness of basic sciences taught to medical students before beginning of the clinical course and practice in higher grades. One method which is evaluated in the present study is early clinical experience. Methods and Materials: In this descriptive study, all medical freshmen were participated in a half day workshop for familiarity with hospital clinical environment. The attitude of the students towards early clinical exposure, profession, and medical education was investigated using a 30- item questionnaire before and after this workshop. Results: Totally, 207 students participated in the present study. Overall, scoring of the program was good to excellent on a five-point Likert scale (93.75%). Most students (89.6%, score =4.25) believed that the program’s content and management was appropriate for them. Conclusions: It was concluded that early clinical experience parallel with theoretical courses can provide a framework for the beneficial and successful integration of the teaching and learning of basic sciences for medical students.[GMJ. 2012;1(2):42-47]